Adaptation of forgotten buildings the example of the ruins of the Kościelec protestant church in Piaski - Gleń, Piotr; Jarocka-Mikrut, Aleksandra (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Small towns in the Lublin Province are abundant with buildings possessed of outstanding historical and architectural values, representing the culture of past generations. Piaski, about 30 km east of Lublin, also boasts some of the remarkable characteristic of small towns. Not only does it feature post-Jewish tenements, but also a palace and complexes of religious buildings situated on its outskirts.
Keywords: zbór kalwiński; bracia polscy; Piaski; Kościelec; rewitalizacja; Protestant church; Polish Brethren; revitalisation